Intercomprehension causes polemics: alterity and heterogeneity in the discourses of singers Anitta and Pitty regarding female sexual behavior - Gonzaga, Juliane de Araujo [UNESP] (Univ Federal Minas Gerais, Fac Letras, 2017)
This article investigates a polemic issue between the Brazilian singers Anitta and Pitty during a television show. The polemic was about the feminine behavior in relation to sexuality. The specific objectives are: (i) to verify how alterity and heterogeneity delimit discursive positions; (ii) to analyze a polemic issue and the use of simulacrums in the intercomprehension process; and (iii) to demonstrate that alterity and heterogeneity materialize some conflicts historically legitimated in the context of sexuality. Placed on the French Discourse Analysis, this research applies the theoretical and methodological arsenal based on the assumptions of Jacqueline Authier-Revuz (1990; 1998) about alterity and enunciative heterogeneity. This work also applies Dominique Maingueneau's reflections (1993; 2005) concerning the primacy of interdiscourse and the polemic as an intercomprehension. The method of analysis is based on the description and interpretation of linguistics expressions (glosses, pronouns, deictics, lexis) that materialize alterity, interdiscourse movements and discourse regulation. In short, the analysis concludes that enunciation is heterogeneously marked and that discursive positions produce polemic situations for it expresses simulacrums, stereotypes and historic conflicts between genders in the context of sexuality.
Keywords: discourse; alterity; heterogeneity; polemic